Penerapan Sistem Informasi Manajemen Online sebagai Sarana Sosialisasi Produk Unggulan Masyarakat di Desa Ngringo, Kecamatan Jaten, Kabupaten Karanganyar - Arif Sutikno; Yudhistiro Pandu W. S.S (Politeknosains, 2018)
The birth of computer and internet technology has presented alternatives in the use of communication media in various sectors, such as promotion and socialization. ICT (Information and Communication Technology) is a continuation of IT (Information Technology). Information and communication technology can be used in the framework of providing information services, because ICT is basically in the form of compiling databases. The purpose of this study is to accelerate accurate and precise information to the public by utilizing WEB-based internet connections as a means of socializing superior products online and mobile, in accordance with site addresses designed to improve economic and social. Successive research methods are qualitative, descriptive and actions where outcomes are in the form of a sustainable system. Computer hardware, software and internet network tools. Product promotion and socialization must use a wide range of media, so that the target of consumers will be more. The IT-based Management Information System is able to access online so that it can be done anywhere as long as it is connected to the internet and provides data security from the risk of loss of documents, damage to documents, and the threat of information / data damage. Thought to provide convenience, effectiveness and efficiency in the promotion and socialization of the products of the partners of the Suryono-Farm Group, one of the forms of modern information use application business. Conclusions in this study note that the use of IT Information Systems through the Website is able to be a marketing information media for catfish production at Suryono Farm, so that people will be easier and faster to find out information and change prices at any time. The mechanism for using Website-based Information Systems at Suryono Farm as Media Marketing information on catfish production, is no longer limited to working hours and facilitates control and changes in data management. Handling the process of entering and updating the marketing information data from catfish production at Suryono Farm can always be automatic updates. This Information System is only as a medium for delivering IT-based information that serves as a service to consumers of catfish production at Suryono Farm.